2009
DOI: 10.1111/j.1600-0404.1997.tb00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory event related potentials in patients with epilepsy on sodium valproate monotherapy

Abstract: ~ event related potentials in patients with epilepsy on sodium valproate 1 monotherapy. 1 . k l a Neurol Scand 1997: 96: 62-64. 0 Munksgaard 1997.Oblecmes -The effects of antiepileptic drugs on event related potentials (EKPs) have been studied, but with contradictory results. In this study we cuamine the effect of sodium valproate (VPA) on ERPs in patients with epilepsy. Materiul and methods -Auditory event related potentials were recorded in 40 patients with idiopathic generalized epilepsy, 20 on monotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The time span between seizure onset and ERP recording needs to be further investigated. Secondly, the effect of antiepileptic drugs (AEDs) may not be neglected [33][34][35]. There was not significant difference in MMN/MMP between the group with monotherapy and that with polytherapy, which was consistent with the previous finding [36].…”
Section: Mmn/mmp Changes In Tle Patientssupporting
confidence: 87%
“…The time span between seizure onset and ERP recording needs to be further investigated. Secondly, the effect of antiepileptic drugs (AEDs) may not be neglected [33][34][35]. There was not significant difference in MMN/MMP between the group with monotherapy and that with polytherapy, which was consistent with the previous finding [36].…”
Section: Mmn/mmp Changes In Tle Patientssupporting
confidence: 87%
“…Similar observations have been reported for valproic acid (VPA). Pana-gopoulos et al found a significantly prolonged P300 latency in patients taking VPA, while no cognitive impairment was observed in children taking VPA 8,20 . Naganuma et al examined auditory ERP in patients with benign childhood epilepsy with centrotemporal spike and found that P300 latency was significantly prolonged in patients receiving CBZ, but Chen et al failed to detect cognitive impairment in children on CBZ 8,21 .…”
Section: Discussionmentioning
confidence: 95%
“…The influence of anti-epileptic medication on P300 remains controversial. [37][38][39][40][41][42] The small number of participants in this study, combined with the use of multiple drugs by many of our patients, makes it difficult to discuss the possible influence of medication on our results. A direct comparison was impossible since the doses of different substances cannot be meaningfully compared.…”
Section: Discussionmentioning
confidence: 99%